TINJAUAN YURIDIS ATAS PEMBENTUKAN HOLDING COMPANY BUMN (STUDI PT.PERKEBUNAN NUSANTARA III MEDAN) - JULIANA BR HUTASOIT (PREMISE LAW JURNAL, 2017)
Holding company is a company which is established to have stocks in one or more companies in order to organize them. The concept of a holding company is beyond legal domain. Its existence is referred to business reality of the merger of companies affiliated to the holding company. In Law No.40/2007 on Limited Liability in which Single Economic Entity doctrine is intended to the holding company liability. The establishment of PTPN III holding company was based on the Goverment Regulation No. 72/2014 which was Operating holding company, stipulated in its Articles of Association.The research problems aere as follows: how about the existence of a holding companny in the legal provisions in Indonesia, how about legal domicile of a holding company and subsidiaries in a holding company, and how about the juridical analysis on the establishment the holding company of BUMN Perkebunan (a case study at PTPN III). The research used juridical empirical and descriptive analysis method. The data were gathered by conducting library research and interviews and conclusion would be drawn.The conclusion of the research is that laws in Indonesia have not regulated the existence of a holding company which coonstitutes an aconomic entity unit that cannot be separated one to another. Juridical relation between a holding company and its subsidiaries is shareholders where holding controls subsidiaries by using limited liability approach. The establishment of the holding company of PTPN III was based on company restructuring policy by conducting rightsizing. The establishment of PTPN III was done by using the concept of controlling subsidiaries embodied in its Articles of Association.Keywords: Holding Company, BUMN, PT.Perkebunan Nusantara III